Determination of Zinc, Cadmium and Lead Bioavailability in Contaminated Soils at the Single-Cell Level by a Combination of Whole-Cell Biosensors and Flow Cytometry - Hurdebise, Quentin; Tarayre, Cédric; Fischer, Christophe; Colinet, Gilles; Hiligsmann, Serge; Delvigne, Frank (Sensors (Basel, Switzerland), 2015)
Zinc, lead and cadmium are metallic trace elements (MTEs) that are widespread in the environment and tend to accumulate in soils because of their low mobility and non-degradability. The purpose of this work is to evaluate the applicability of biosensors as tools able to provide data about the bioavailability of such MTEs in contaminated soils. Here, we tested the genetically-engineered strain Escherichia coli pPZntAgfp as a biosensor applicable to the detection of zinc, lead and cadmium by the biosynthesis of green fluorescent protein (GFP) accumulating inside the cells. Flow cytometry was used to investigate the fluorescence induced by the MTEs. A curvilinear response to zinc between 0 and 25 mg/L and another curvilinear response to cadmium between 0 and 1.5 mg/L were highlighted in liquid media, while lead did not produce exploitable results. The response relating to a Zn2+/Cd2+ ratio of 10 was further investigated. In these conditions, E. coli pPZntAgfp responded to cadmium only. Several contaminated soils with a Zn2+/Cd2+ ratio of 10 were analyzed with the biosensor, and the metallic concentrations were also measured by atomic absorption spectroscopy. Our results showed that E. coli pPZntAgfp could be used as a monitoring tool for contaminated soils being processed.